Impact of development of infrastructure for charging electric vehicles on power demand in the national power system = Wpływ rozwoju infrastruktury do ładowania pojazdów elektrycznych na zapotrzebowanie na moc w krajowym systemie elektroenergetycznym - Szabłowski, Łukasz; Bralewski, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The following paper focuses on the electric vehicles sector development and its possible influence on power system load in Poland. The goal is to estimate the increase of power demand resulting from the electric cars charging. First of all, the current legal environment, which provides a framework for the e-mobility sector evolution, was described.
Keywords: e-mobility; electric vehicles; electric vehicles charging; National Power System; samochody elektryczne; ładowanie samochodów elektrycznych; Krajowy System Elektroenergetyczny